The Effect of Online Learning Using Quizizz Application to Improve English Reading Skills of Higher Education Students - Candra Hadi Asmara; Ribeh Najib Muhammad; Qothrunnada Almubarokah (Universitas Sarjanawiyata Tamansiswa, 2022)
In this current era of technology, the use of online-based learning media that suits the needs of students can improve their learning skills, so teachers need to know the media criteria that must be applied to attract students' learning interests and those materials can be well received by students. Quizizz is one of those quiz-shaped and 4.0-based apps which is already popular among higher education. Quizizz can be used to train reading skills, especially students in English because in the application many features allow students to enhance their reading interest. The purpose of this study is that researchers will identify the influence of the Quizizz application on students' reading ability. The method used in this study was experimental. The instrument used is a test sheet. For data collection techniques conducted is to conduct a pre-test at the beginning of learning and a post-test at the end of learning, so that it can be seen the influence of the application of Quizizz application, in this case, improve students' English reading skills.